2016
DOI: 10.4067/s0034-98872016001200002
|View full text |Cite
|
Sign up to set email alerts
|

Participación de los virus respiratorios en la neumonía del adulto inmunocompetente adquirida en la comunidad

Abstract: The use of molecular diagnostic techniques expanded the detection of respiratory viruses in immunocompetent adults hospitalized with CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…With the development of the molecular diagnostic techniques and wide clinical applications, respiratory viruses (RVs), including the influenza virus (IFV), human rhinovirus (hRV), respiratory syncytial virus (RSV), human metapneumovirus (hMPV), human parainfluenza virus (hPIV), human adenovirus (hAdV), enterovirus (EV) and human coronaviruses (hCoV), have been increasingly recognized to play an important role in the occurrence of CAP. 3 Previous research reported the prevalence of RVs in CAP to be about 20–50%, 4 , 5 sometimes even higher than that of Streptococcus pneumoniae , 6 which was regarded as the most common pathogen in the patients with CAP. A meta-analysis including 31 studies indicated that the pooled proportion of patients with viral infection was 24.5% (95% confidence interval (CI) 21.5–27.5%); while the studies that obtained lower respiratory samples in >50% of the patients reported the proportion to be 44.2% (95% CI 35.1–53.3%).…”
Section: Introductionmentioning
confidence: 97%
“…With the development of the molecular diagnostic techniques and wide clinical applications, respiratory viruses (RVs), including the influenza virus (IFV), human rhinovirus (hRV), respiratory syncytial virus (RSV), human metapneumovirus (hMPV), human parainfluenza virus (hPIV), human adenovirus (hAdV), enterovirus (EV) and human coronaviruses (hCoV), have been increasingly recognized to play an important role in the occurrence of CAP. 3 Previous research reported the prevalence of RVs in CAP to be about 20–50%, 4 , 5 sometimes even higher than that of Streptococcus pneumoniae , 6 which was regarded as the most common pathogen in the patients with CAP. A meta-analysis including 31 studies indicated that the pooled proportion of patients with viral infection was 24.5% (95% confidence interval (CI) 21.5–27.5%); while the studies that obtained lower respiratory samples in >50% of the patients reported the proportion to be 44.2% (95% CI 35.1–53.3%).…”
Section: Introductionmentioning
confidence: 97%
“…Dentro do espectro infeccioso do trato respiratório, os agentes virais apresentam maior importância clínica, principalmente pela possibilidade gerarem epidemias extensas e pandemias recentes (Rodrigues et al, 2019). No Chile, estudo clínico prospectivo descritivo realizado com 240 pacientes adultos internados por um episódio de pneumonia adquirida na comunidade demonstrou que os virus foram responsáveis em causar pneumonia nesse grupo, ocorrendo em indivíduos que apresentaram múltiplas comorbidades, com incremento de internação na Unidade de Terapia Intensiva (UTI) e mortalidade hospitalar (Peñafiel et al, 2016).…”
Section: Discussionunclassified
“… 1 , 2 As a result of advances in nucleic acid diagnostics and its clinical applications, respiratory viruses (RVs) have been increasingly recognized as a major player in the occurrence of CAP. 3 , 4 Previous research has indicated that the prevalence of RVs in CAP ranges from 20% to 50%, 5 , 6 which is eventually higher than that of Streptococcus pneumoniae , 7 the most common pathogen in patients with CAP. One European meta-analysis, comprising 21 studies, has indicated that the pooled proportion of RVs in patients with CAP is 22% [95% confidence interval (CI) of 18–27%].…”
Section: Introductionmentioning
confidence: 99%